Universalization of healthcare for non-communicable diseases in India - Promise of health and wellbeing, insurance for universal health coverage - Bijit Biswas; Abu Bashar MD; Muralidhar M Kulkarni; Imran Ahmed Khan (Wolters Kluwer Medknow Publications, 2023)
Noncommunicable diseases (NCDs) pose a significant global health and economic burden, necessitating universal health coverage (UHC). Out-of-pocket (OOPs) payments for healthcare, particularly in low- and middle-income countries lacking social protection and health insurance, contribute to impoverishment and catastrophic expenditure. This scoping review aimed to assess the state of UHC for NCDs in India, including the progress made, coverage of government health insurance schemes, challenges faced, and their potential solutions. A literature search was performed in major databases such as PubMed, Ovid, Web of Science, Embase, Cochrane Library, and Google Scholar using appropriate keywords. Findings indicated that UHC remains a distant dream in India with a disproportionately high NCD burden and a substantial portion of health-care expenses (80% outpatient, 40% inpatient) relying on OOP expenditures, causing financial hardship. Limited universal social security exacerbates health-care access challenges. The coronavirus disease-2019 pandemic has further hindered NCD services and UHC progress. The Ayushman Bharat program, featuring health and wellness centers and the Pradhan Mantri Jan Arogya Yojana, aims to address primary health-care needs and provide NCD coverage in India. Despite this, challenges persist, including inadequate availability of essential medicines and technologies in health-care facilities, as well as gaps in rural health-care access. Telemedicine services like "eSanjeevani" have been implemented to improve access in remote areas. To achieve UHC for NCDs in India, it is crucial to strengthen primary health-care, ensure medicine availability, enhance human resources, establish a referral system, address social determinants, and implement social protection.